The Effect of Reinforcement, Expanded Polystyrene (EPS) and Fly Ash On The Strength of Foam Concrete - Rosli, M.F.; Rashidi, A.; Ahmed, E.; Sarudu, N.H. (Universiti Malaysia Sarawak, 2011)
Foam concrete is a type of lightweight concrete. The main characteristics of foam concrete are its low density and thermal conductivity. Its advantages are that there is a reduction of dead load, faster building rates in construction and lower haulage and handling costs. This research was conducted to investigate the compressive strength and flexural strength of reinforced foam concrete. The use of fly ash and Expanded Polystyrene (EPS) as cement and sand replacement were also included in the production of reinforced foam concrete. There were two types of reinforcements used to reinforce the foam concrete namely plastic and wire mesh. Physical failure mode, compressive strength and flexural strength of samples were compared and analyzed. The replacement percentages for both fly ash and EPS were varied between 0-50% and 0-40% respectively. The study showed that it is feasible to reinforce the foam concrete and the best result was obtained from wire mesh reinforcement. The study also showed that the optimum replacement level for both fly ash and EPS was 30% based on compressive and flexural strength results.